Developing Mathematical Students Worksheet Based On Islamic Values Using Contextual Approach - Choirudin, Choirudin; Ningsih, Eka Fitria; Anwar, M. Saidun; Choirunnisa, Ani; Maseleno, Andino (International Journal on Emerging Mathematics Education, 2019)
Development of worksheets looks like the beginning of the problems found in schools, students have difficulty to understanding mathematical material both calculation concepts and moral values that have not been well organized. Worksheet designed with using a contextual approach which contains collaboration between material and verses relating to the used material, so that moral values related to the material are obtained and equipped with the application of moral values in the form of problem examples. After being designed, product is developed to be LKPD. The study objectives include: To develop a Mathematics LKPD based on Islamic values on the subject of algebraic. As a result of the study, the development of Student Worksheet (LKPD) based on Islamic values using a contextual approach to the subject of algebraic in class VII of the Qur'an Science Junior High School Minhajuth Thullab Pekalongan. The research uses the 4D development model consists of 4 main stages: Define, Design, Develop and Disseminate. The response of teachers to LKPD based on Islamic values with using a contextual approach on the subject of the algebra score 82% with very interesting criteria. The responses of students to LKPD obtained a score of 80 % with very decent criteria.